2018
DOI: 10.1002/pep2.24083
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutics of Alzheimer's diseases: New insights into the neuroprotective role of trehalose‐conjugated beta sheet breaker peptides

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disease with no cure. The conversion of the amyloid‐β (Aβ) peptide into soluble oligomers has recently become recognized as playing a key role in AD pathogenesis. Thus, prevention and therapeutic strategies against AD focus on modulating Aβ levels aiming also at stabilizing Aβ's monomeric status or inhibiting the peptide's self‐assembly. Peptide‐based inhibitors may provide a reasonable alternative to chemical small molecules. We report herein further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Such evidence suggests, once more, that these interactions occur in the solution phase and may play a role in the early events of the Aβ 42 aggregation process. As reported in our previous works, 16,27 the identification of proteolysis resistant peptides fragments by mass spectrometry may reveal the binding region of Aβ 42 to specific molecules. Indeed, cleavage of the peptide bonds by a protease is rapid in easily accessible unstructured regions of a polypeptide, whereas the steric hindrance of other molecules at the cleavage sites should affect the rate of hydrolysis.…”
Section: ■ Results and Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Such evidence suggests, once more, that these interactions occur in the solution phase and may play a role in the early events of the Aβ 42 aggregation process. As reported in our previous works, 16,27 the identification of proteolysis resistant peptides fragments by mass spectrometry may reveal the binding region of Aβ 42 to specific molecules. Indeed, cleavage of the peptide bonds by a protease is rapid in easily accessible unstructured regions of a polypeptide, whereas the steric hindrance of other molecules at the cleavage sites should affect the rate of hydrolysis.…”
Section: ■ Results and Discussionmentioning
confidence: 69%
“…Selective targeting of Aβ’s fibrillogenesis should not interfere with the physiological function of APP as well as other proteins involved in the production of Aβ monomers, whose physiological beneficial role has been recently reported . Several small molecules, metal chelators, carbohydrate-containing compounds, and short peptides have been identified as inhibitors of amyloid aggregation. In particular, the clinical evidence of an abnormal metal ion interaction with Aβ in AD has promoted studies aimed at developing potential therapeutic strategies by using metal chelators or antioxidant compounds that target aberrant metal distribution and the adverse consequences of metal induced oxidative stress in AD. The finding that the hydrophobic core at residues 16–20 of Aβ (KLVFF) is crucial for the formation of β-sheet structures has stimulated the investigation of the KLVFF peptide as an inhibitor of Aβ 42 fibrillogenesis . Some papers in the past reported that the KLVFF peptide, by binding the homologous sequence in full-length Aβ, can prevent at aggregation into fibrils ,, and this ability is maintained after conjugation to different scaffolds including oligolysines, cyclodextrins, dendrimers, or porphyrins. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that P5 was most effective in inhibiting tau aggregation, followed by P4 and KLVFF, whereas LPFFD, P3, and P6 showed no inhibition (Figure A). Similarly, amyloid-β aggregation inhibition was studied by LPFFD derivatives, , where these peptides reduced fluorescence, indicating inhibition of aggregation. LPFFD is a β-breaker that has no role in inhibiting tau aggregation in our studies, whereas KLVFF prevents tau aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…All these findings strongly suggest that trehalose-CIGB552 interactions may take place in the therapeutic formulation, inhibiting peptide fibrillogenesis. Trehalose-peptide conjugates have already been shown to act as inhibitors of amyloid fibrillation, 39 enhancers of resistance towards proteolytic degradation, 40 and protectants against thermal denaturation of proteins. 41 These ideas pave the way for explaining the higher cytotoxic activity of CIGB552 in its therapeutic formulation, suggesting that peptide fibrillation may inhibit its therapeutic activity.…”
Section: Discussionmentioning
confidence: 99%